Evaluación de la Capacidad de Adsorción de Arcillas Naturales Mediante Cinética e Isotermas de Adsorción en la Remoción de Colorantes - Cuesta Zúñiga, Erick Efraín (2022)
The objective of this study is to evaluate the potential of two natural clays to remove the dyes Basic Marine Blue 2 RN (cationic) and Drimaren Yellow CL-2R (anionic). The variables evaluated were the initial concentrations, the adsorbent dose and the variation of the initial pH. The experimental isotherm data analyzed using Langmuir, Freundlich and Temkin models. Both clays were effective in removing both cationic and anionic dye at acidic pH values. However, the red clay maintained its efficiency in removing both cationic and anionic dye over a wider pH range. The Langmuir model obtained the best fit with a maximum monolayer adsorption capacity of 1.69 mg/g for the white clay and 2.80 mg/g for the red clay, using the cationic dye. In the case of the anionic dye the maximum adsorption capacity in monolayer was 1.02 mg/g for white clay and 1.84 mg/g for red clay, using the anionic dye. The pseudo-second order kinetic model was found to describe the dye adsorption data on the two adsorbents very well.